Acquired rearrangement of an amplified epidermal growth factor receptor (EGFR) gene in a human glioblastoma xenograft - Goike, H. M.; Asplund, A. C.; Pettersson, E. H.; Liu, L.; Sanoudou, D.; Collins, V. P. (J Neuropathol Exp NeurolJ Neuropathol Exp NeurolJ Neuropathol Exp Neurol, 1999)
Amplification of the epidermal growth factor receptor (EGFR) occurs in about 40% of human glioblastomas. In half of these cases, rearrangements of the amplified gene result in aberrant transcripts and proteins. The most frequent rearrangement affects the external domain of the receptor and results in nonbinding of ligand and constitutive activity. Less frequent rearrangements involve changes resulting in the loss of cytoplasmic amino acid sequences necessary for downregulation of the receptor following ligand binding. Here we report the development and selection for a rearranged amplified EGF receptor, which lacks cytoplasmic amino acid sequences in a human glioblastoma xenograft. An identical aberration has previously been reported in glioblastoma tissue. The patient tumor material, as well as the first passages of the xenograft showed amplification of the EGFR gene, but no evidence of gene rearrangement or an aberrant transcript. Interphase FISH data show the amplified gene on double minutes. Between passages 3 and 16, the growth rate of the xenograft almost doubled, the rearranged amplicon became dominant, as did the aberrant transcript, indicating selection under these conditions.
Keywords: *Gene Amplification/genetics; *Gene Rearrangement/genetics; *Neoplasm Transplantation; *Transplantation, Heterologous; Animals; Base Sequence/genetics; ErbB Receptors/*genetics; Glioblastoma/*genetics; Humans; In Situ Hybridization, Fluorescence; Mice; Mice, Inbred C57BL; Mice, Nude; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger/genetics